2017
DOI: 10.1039/c6ra27288f
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin based nano-sized imprinted polymer as an efficient modifier for the design of a potentiometric copper carbon paste electrode

Abstract: In this study, a new carbon paste electrode (CPE) modified with porphyrin-based ion imprinted polymer (IIP) was designed and applied for the potentiometric determination of Cu2+ions in aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This makes MIPs highly competitive 20 for selectively recognizing the target analyte in the presence of structurally similar molecules. Moreover, MIP nanostructures [21][22][23] offer the advantages of higher selectivity and sensitivity due to the presence of a larger number of tailored interaction sites and therefore, considered as efficient sensor interfacial coatings for a wide range of analytes. [24][25][26] Moreover, nanosized MIPs exhibited shorter response time due to faster mass transfer rates.…”
Section: Several Methods Have Been Developed For the Determination Ofmentioning
confidence: 99%
“…This makes MIPs highly competitive 20 for selectively recognizing the target analyte in the presence of structurally similar molecules. Moreover, MIP nanostructures [21][22][23] offer the advantages of higher selectivity and sensitivity due to the presence of a larger number of tailored interaction sites and therefore, considered as efficient sensor interfacial coatings for a wide range of analytes. [24][25][26] Moreover, nanosized MIPs exhibited shorter response time due to faster mass transfer rates.…”
Section: Several Methods Have Been Developed For the Determination Ofmentioning
confidence: 99%
“…The results indicated that the imprinted polymer was remained stable aer template elimination process using acid solution. 13,36,37 Thermogravimetric analysis. The TGA curve and dTG plot of MIP4 and NIP4 are shown in Fig.…”
Section: Mip4 Andmentioning
confidence: 99%
“…Additionally, the hyphenation of ion-imprinted polymers (IIPs) prepared using IIT and other sensing technology, such as electrochemistry, for separation and detection also possesses expansive prospects. [27][28][29] However, ion imprinting technology still has many disadvantages for the detection of As(III), among which the most important is that the adsorption capacity is generally low. 30,31 Fortunately, mesoporous adsorbents can effectively improve the adsorption capacity of ion-imprinted polymers for target heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%